THE EFFECTIVENESS OF IMPLEMENTING ORIENTATION AND PLACEMENT IN PRODUCING QUALIFIED HR AT MA FATHAN MUBINA - Hakim, Luqmanul; Abdul Kholik; Siti Uluwiyah; Reffi Ananda Dharmawan; Siti Aisyah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to find out what kind of orientation program is implemented by Madrasah Aliyah Fathan Mubina in order to get qualified Educators and Educational Staff in order to improve the quality of human resources and strive for professionalism. This research method uses a qualitative approach. Meanwhile, the source of data in this study comes from primary data, namely interviews and sources from secondary data, namely books and journals that can strengthen this research. The results showed that the steps and strategies taken by MA Fathan Mubina in orientation were to carry out environmental orientation independently by implementing a probationary period of 3 months, under the supervision of the school leadership. And MA Fathan Mubina places employees according to the abilities of the employees and the needs of the school. It can be concluded that the results of orientation can streamline time because employees already know each of their jobs and can adapt to their school environment, both in terms of familiarity with employees, as well as in completing a job.